De-dollarization: The global payment infrastructure and wholesale central bank digital currencies - Jörg Mayer (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
Traditional trust-related de-dollarization motives have gained additional impetus from the declining share of the United States in global output, recent upheaval in dollar bond markets, geopolitical tensions, and a "weaponization" of the dollar. Several institutional innovations by China and the BRICS demonstrate the demand for de-dollarization but do not offer credible alternatives to the dollar's value characteristics. By contrast, new financial technology, including distributed ledger technology (DLT), and related changes in cross-border payment infrastructure could reduce the network effects that have sustained dollar dominance. By allowing for leaner cross-border payment infrastructures and an easier, cheaper, and more transparent use of non-dollar currencies in cross-border payment and settlement, DLT-based wholesale central bank digital currency (wCBDC) platforms with a foreign-exchange conversion layer may indicate a direction of travel. Pilots of multicurrency wCBDC-platforms indicate how to enable interoperability and reduce exposure to foreign-exchange risk. Regarding institutional (legal, regulatory, and supervisory) frameworks required to fully benefit from infrastructural changes, interlinking common multicurrency wCBDC-platforms among limited numbers of like-minded central banks to form an interoperable hub-and-spoke global wCBDC-system could minimize fragmentation risks while accommodating diverging governance preferences, e.g., concerning data protection and developmental aspirations. By augmenting macroeconomic autonomy and reducing the need for costly dollar reserves, de-dollarization promises greater benefits for countries with non-dominant currencies. These countries should sit at the table when outstanding questions on interoperability and related economic, technical, legal and governance questions regarding multicurrency wCBDCs platforms are answered.
Keywords: 330